SOIL IMPROVEMENT ANALYSIS WITH PRELOADING AND PREFABRICATED VERTICAL DRAIN (PVD) USING FINITE ELEMENT METHOD - HARRY PRATAMA (NIM : 25008016); Pembimbing : Ir. Erza Rismantojo, MSCE, Ph.D., JACKI
Analysis of soil settlement by using finite element method of PLAXIS 7.1.1 obtained mixed results, ie 1.08 m for the Mohr-Coulomb model, 0.75 m for the Hardening Soil model, and 0.64 m for the Soft Soil model. The comparison of the result with field settlement plate, that only 0.4 m and the result of 1D Terzaghi consolidation analysis, showed that the settlement actually happens on the field is smaller. This is caused by the reduced value of the coefficient of consolidation of the soil during reclamation process. From the analysis results, known that the Soft Soil model is more accurate in modeling of soil compared with Mohr-Coulomb model and Hardening Soil model. That because Soft Soil model using consolidation input parameters such as compression index (Cc) and swelling index (Cs) in its calculation, so the Soft Soil model provides a fairly accurate result on the calculation of the soft soil compared with the Hardening Soil model and the Mohr-Coulomb model.